The impact of allergen exposure and specific immunotherapy on circulating blood cells in allergic rhinitis - Jordakieva, Galateja; Jensen-Jarolim, Erika (The World Allergy Organization journal, 2018)
Allergic rhinitis (AR) is an IgE-mediated inflammatory disease of the nasal mucosa with well described local immune responses during allergen exposure. The frequent association of AR with general extra-nasal symptoms and other allergic conditions, such as conjunctivitis and asthma, however, support a more systemic disease impact. In addition to acute elevation of soluble inflammatory mediators in periphery blood, a growing number of studies have reported changes in circulating blood cells after specific nasal allergen challenge or environmental allergen exposure. These findings imply an involvement of specific blood leukocyte subsets, thrombocytes and recently, erythrocytes. This review summarizes the circulating blood cell dynamics associated with allergen exposure in AR subjects reported so far. Additionally, the impact of therapy, particularly allergen-specific immunotherapy (AIT), the only currently available causal treatment reducing AR-related symptoms, is further considered in this context.